(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
Formation of complex between cobalt ion (Co2+) and isoleucine (Ile) with composition 1:1, which reveals itself as a model catalyst for decay of cumene hydroperoxide (ROOH) in the studied Co2++Ile+ROOH+H2O system, has been established by kinetic method. The kinetic equation of rate of catalytic decay of ROOH under the action of [Cо∙Ile]+ complex catalyst has been derived: W0 = –d[ROOH]0/dt = Kcat [Cо2+]0[Ile]0[ROOH]0 = Keff[ROOH]0. Temperature dependence of the effective rate constant (Keff=Kcat[Cо2+]0[Ile]0) of decay of ROOH in the interval 323–353 K is expressed by Arrhenius equation (Eeff in kJ/mol): Keff = (2.50±0.02)108 exp[–67.0 ± 0.3/RT] min-1.